FORMALISASI SYARIAT ISLAM DALAM PANDANGAN KIAI NU STRUKTURAL - HM, Sahid (LP2M IAIN Mataram, 2011)
The objective of this research is to analyze the view of the NU kyai, who are the board members of the organization. The focus of the study is on the formalization of Islamic criminal law. The study maps out the typology of thought of the NU kyai regarding Jakarta Charter in the state constitution, the raising of sharÃ®a regulations and by laws in several regions, and the endorsement of Anti Pornography Act. The study shows that the NU kiai conceive of the formalization of Islamic Sharia in Indonesia regarding Islamic criminal law within the framework of preserving the nation and its socio-culture, namely defending the unity of Indonesia and its Pancasila as an ideology. In this perspective, the relation of the state and religion is symbiotic where both are mutually dependent. However, they differ in terms of giving priority between symbiotic formalism and symbiotic substantive within the state-religion relation. Regarding socio-cultural context, their perceptions come under three categories: idealism, transformism, and pragmatism.